Control of Immediate Early Gene Expression for Human Cytomegalovirus Reactivation - Collins-McMillen, Donna; Kamil, Jeremy; Moorman, Nathaniel; Goodrum, Felicia (Frontiers in Cellular and Infection Microbiology, 2020)
Human cytomegalovirus (HCMV) is a beta herpesvirus that persists for life in the majority of the world’s population. The persistence of HCMV in the human population is due to the exquisite ability of herpesviruses to establish a latent infection that evades elimination by the host immune response. How the virus moves into and out of the latent state has been an intense area of research focus and debate. The prevailing paradigm is that the major immediate early promoter (MIEP), which drives robust expression of the major immediate early (MIE) transactivators, is epigenetically silenced during the establishment of latency, and must be reactivated for the virus to exit latency and re-enter productive replication. While it is clear that the MIEP is silenced by the association of repressive chromatin remodeling factors and histone marks, the mechanisms by which HCMV de-represses MIE gene expression for reactivation are less well understood. We have identified alternative promoter elements within the MIE locus that drive a second or delayed phase of MIE gene expression during productive infection. In the context of reactivation in THP-1 macrophages and primary CD34+ human progenitor cells, MIE transcripts are predominantly derived from initiation at these alternative promoters. Here we review the mechanisms by which alternative viral promoters might tailor the control of viral gene expression and the corresponding pattern of infection to specific cell types. Alternative promoter control of the HCMV MIE locus increases versatility in the system and allows the virus to tightly repress viral gene expression for latency but retain the ability to sense and respond to cell type-specific host cues for reactivation of replication.